2007
DOI: 10.1002/mus.20797
|View full text |Cite
|
Sign up to set email alerts
|

Limited expression of slow tonic myosin heavy chain in human cranial muscles

Abstract: Recent reports of slow tonic myosin heavy chain (MHCst) in human masticatory and laryngeal muscles suggest that MHCst may have a wider distribution in humans than previously thought. Because of the novelty of this finding, we sought to confirm the presence of MHCst in human masticatory and laryngeal muscles by reacting tissue from these muscles and controls from extraocular, intrafusal, cardiac, appendicular and developmental muscle with antibodies (Abs) ALD-58 and S46 considered highly specific for MHCst. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 31 publications
2
44
0
Order By: Relevance
“…The existence of fibers expressing a specific laryngeal myosin isoform has been reported in a number of studies, but its identification is still controversial (176,344,883). There are also contrasting evidence in favor of the expression of the slow tonic isoform, although this does not bear a direct relation with the presence of multiple innervation (344,748). Actually, many fibers of thyroarytenoid and lateral cricoarytenoid show several neuromuscular junctions spread along their length, but each fiber seems to be in contact with only one motor neuron (481).…”
Section: Head and Neck Musclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of fibers expressing a specific laryngeal myosin isoform has been reported in a number of studies, but its identification is still controversial (176,344,883). There are also contrasting evidence in favor of the expression of the slow tonic isoform, although this does not bear a direct relation with the presence of multiple innervation (344,748). Actually, many fibers of thyroarytenoid and lateral cricoarytenoid show several neuromuscular junctions spread along their length, but each fiber seems to be in contact with only one motor neuron (481).…”
Section: Head and Neck Musclesmentioning
confidence: 99%
“…This analogy was confirmed by the finding that bag fibers are reactive with polyclonal antibodies to avian slow myosin, which stain slow-tonic fibers of amphibians and multiply innervated slow-tonic fibers in mammalian EOMs but not slow-twitch mammalian muscle fibers (85,86). This immunoreactivity is shared by some monoclonal anti-chicken myosin antibodies, the most specific being S46 (748), and has been widely used as a specific intrafusal fiber marker in studies of muscle spindle development (see sect. V).…”
Section: Muscle Spindlesmentioning
confidence: 99%
“…The human MHC-ma gene produces a truncated and nonfunctional protein but is still transcribed in masseter [Stedman et al, 2004]. MHCst is demonstrated by immunohisotochemistry (IHC) in extraocular muscles, but its presence in other head and neck muscles is in dispute Brandon et al, 2003;Sokoloff et al, 2007a;Sokoloff et al, 2009]. To our knowledge, MHC-st has not been studied by PCR, which enables identification of low levels of mRNA expression.…”
mentioning
confidence: 99%
“…muscles with their origin and insertion within the tongue body) have identified MHC-beta, MHC-2a and MHC-2x in the adult macaque and human, and MHC-2b in macaque [Stal et al, 2003;Smith et al, 2006;Sokoloff et al, 2007b;Sokoloff et al, 2009], but have found no or limited developmental and unconventional MHC [Sokoloff et al, 2007a;Sokoloff et al, 2009]. However, these studies are limited by discordance in reports of antibody specificities [Liu et al, 2002;Mu et al, 2004;Sokoloff et al, 2007b], the limited availability of antibodies specific for MHC-alpha and, with the exception of one test for MHC-st [Sokoloff et al, 2007a], no study of unconventional MHC in intrinsic tongue muscles. Electrophoresis studies of MHC in tongue muscles of the adult mouse and rat have identified MHC-2a, MHC-2b and MHC-2x and no or limited MHC-beta, MHC-emb and MHC-neo [Brozanski et al, 1993;Hartmann et al, 2001;Agbulut et al, 2003], but may not allow confident determination of MHC with similar migration mobilities, such as MHCneo and MHC-emb [Brozanski et al, 1993;Lloyd et al, 1996].…”
mentioning
confidence: 99%
See 1 more Smart Citation